Mycorrhizal Inoculation for Growth Enhancement and Improvement of the Water Relations in Mangosteen (Garcinia Mangostana L.) Seedlings - Muhamad, Masri (1997)
Mangosteen (Garcinia delicious fruits of Malaysia and has great potential for commercial development. However, the long juvenile period resulting from the extremely slow growth of the seedlings renders itself an unattractive propcsition for cultivation on a large scale. Accelerating the growth rate of mangosteen seedlings is therefore an important prerequisite for the extensive commercialisation of this crop. Poorly developed root system characterised by unbranched, coarse and lack of laterals strongly correlated to the slow growth. Such root characteristics offer great opportunity for colonisation by arbuscular mycorrhizas (AM). The main objective of this study is therefore, to promote seedling growth through symbiotic associations between AM fungi and mangosteen roots. Results of inoculation studies have shO'Ml that mangosteen seedlings responded to AM infection with more than 60% of the total root length being infected. Introduced AM fungi caused tremendous improvements in the plant growth. Total dry biomass was 40%-64% and net assimilation rate was 30%- 40% higher than the uninoculated seedlings. AM inoculated plants also had 20%-40% more leaves that give 35%-65% greater leaf area compared to the uninoculated seedlings. Stomatal resistance, transpiration rates and chlorophyll content were also Significantly improved by mycorrhizal infection. Improvements in plant growth were primarily due to greater uptake of immobile nutrients, particularly phosphorus (P), zinc (Zn) and copper (Cu). Phosphorus, Zn and Cu uptakes by mycorrhizal plants were 67%-88%, 50%-93% and 53%-59% greater than the uninoculated plants, respectively. Colonisation Significantly induced greater root length density (RLD), root branching density (RBD) and number of root tips with RLD, RBD and number of root tips of AM plants ranged 58%-87%, 20%-30% and 22%-25% respectively greater compared to the uninoculated seedlings. Mycorrhizal rnangosteens were also more tolerant to water stress. They CQuid maintain higher stomatal conductance and photosynthesis at lower moisture status suggesting lower leaf water potentials at which stomata closes. Such ability indicates a more efficient stomatal regulation by AM plants